CHRONOTHERAPY OF HYPERTENSION: CURRENT STATE OF THE SCIENTIFIC PROBLEM - V. M. Gorbunov; E. Y. Fedorova; E. V. Platonova (Рациональная фармакотерапия в кардиологии)
Recently, more and more attention has been  paid to the chronotherapy of arterial hypertension (HT). This method provides an opportunity to improve the treatment efficacy by non-traditional regimes of antihypertensive drug intake. The new findings concerning a high prognostic value of the night-time blood pressure (BP) and night BP fall stimulate the interest in chronotherapy of HT. This method is very easy to use, and the evidences of its high efficacy are growing. The advantages and limitations of two potential chronotherapy approaches are discussed in detail.MAPEC was the largest project which investigated the possibility of cardiovascular complications risk reduction by normalizing the circadian rhythm of BP due to the bed-time administration of antihypertensive drugs. The authors obtained impressive results – more than a double reduction of cardiovascular complications risk in the chronotherapy group.  However, the study had serious limitations: ethnically homogeneous population, the lack of independent verification of endpoints and adverse  events,  and inconvenience of 48-hour BP monitoring.The currently available scientific information concerning advantages of HT chronotherapy needs  further confirmation in the carefully designed multi-centre prospective studies. According to the authors’ opinion, illustrated by their original data, the relatively small and short studies are still important. Such trials allow using more nuanced methodological approaches, such as a double blind or cross-over design and comparison of the pharmacokinetics of antihypertensive drugs in the morning and evening administration.